TOURISM STAKEHOLDERS' COLLABORATION STRATEGIES AND ORGANIZATIONAL PERFORMANCE IN NORTHERN NIGERIA: A STUDY OF THE 2024 GLOBAL ENTREPRENEURSHIP WEEK (GEW) - Joseph Sunday Etuk; Bere Korka Kobani (Journal Park Publishing, 2025)
Tourism plays a critical role in economic diversification and sustainable development, yet its full potential remains largely untapped in Northern Nigeria due to fragmented stakeholder collaboration. This study examines the impact of tourism stakeholders’ collaboration strategies—joint marketing initiatives, resource sharing, and coordinated event planning—on organizational performance in the context of the 2024 Global Entrepreneurship Week (GEW), which was successfully hosted across seven Northern Nigerian states. Using a descriptive-correlational research design, data were collected from 94 registered tourism businesses that actively participated in GEW 2024. Pearson’s correlation analysis was employed to assess the relationship between collaborative strategies and key performance indicators, namely sales revenue and customer base growth. Findings revealed that coordinated event planning exhibited the strongest positive relationship with organizational performance, followed by resource sharing and joint marketing initiatives. However, engagement in joint marketing and resource-sharing efforts remained low, highlighting a critical gap in structured collaboration among tourism stakeholders. The study underscores the need for sustained partnerships beyond major events, emphasizing the importance of government-led incentives, digital collaboration, and structured tourism alliances to enhance long-term sectoral growth.
Keywords: Event Planning, Joint Marketing, Organizational Performance, Resource Sharing, Tourism Stakeholders.